Effect of footwear modifications on oscillations at the Achilles tendon during running on a treadmill and over ground: A cross-sectional study - Meinert, I.; Brown, N.; Alt, W. (PLOS ONE, 2016)
Background: Achilles tendon injuries are known to commonly occur in runners. During running repeated impacts are transferred in axial direction along the lower leg, therefore possibly affecting the oscillation behavior of the Achilles tendon. The purpose of the present study was to explore the effects of different footwear modifications and different ground conditions (over ground versus treadmill) on oscillations at the Achilles tendon.